Experimental investigation of maldistribution characteristics of gas‐liquid two-phase flow in a horizontal pipeline - Wei, Na; Jiang, Lin; Fan, Shuanshi; Liu, Anqi; Li, Haitao; Zhang, Shenghui; Zhang, Chao; Xue, Jin (Frontiers in Earth Science, 2022)
In the flow distribution of oil and gas gathering and transportation system, the flow pattern, inertia force, gravity and other factors will lead to uneven flow distribution of each outlet pipe, which will seriously affect the economy and safety of the gathering and transportation system. Therefore, it is of great significance to analyze the characteristics of gas-liquid two-phase flow in horizontal pipeline. For this reason, an experimental device for maldistribution control of gas-liquid two-phase flow is developed in this paper. In order to solve the problem of flow maldistribution in gas-liquid two-phase flow pipe, the test experiments of maldistribution control under the conditions of three flow patterns (stratified flow, slug flow and annular flow) are carried out. Through experiments, we revealed the flow pattern and the control law of liquid maldistribution and gas maldistribution with or without flute tube, and formed the maldistribution control scheme of gas-liquid two-phase flow in horizontal pipeline. It is found that the horizontal manifold without flute tube is more beneficial to the control of average liquid maldistribution degree under the condition of slug flow pattern, and it is more beneficial to the control of average gas maldistribution degree without flute tube and annular flow pattern. Without the function of flute tube and annular flow pattern, it is beneficial to the control of maldistribution flow of gas-liquid two-phase average. The findings of this research can be used as a reference for the field maldistribution control of oil and gas gathering and transportation system.